Epidemiology and management of parasitic infestations in Indian major carps in extensive culture systems of Andhra Pradesh, India - BALAKRISHNA, CH; RAO, B MADHUSUDHANA; REDDY, A DEVIVARAPRASAD; DHARMAKAR, P; KUMAR, N RANJIT; CHINNAMNAIDU, D; LAKSHMI, K BHAGYA; NEELAVENI, S; KUMAR, S KIRAN; KARUNASREE, E; PRASAD, J V (The Indian Journal of Animal Sciences, 2024)
The occurrence of parasitic infestations in Indian major carps (IMCs) culture systems are seen regularly and is regarded as one the major bottle neck in fresh water fish culture practices causing significant loss to farmers. This study aimed to isolate and identify parasitic threats affecting IMCs in community and panchayat tanks, by characterizing the severity of infestations. The investigation spanned four distinct sites, viz. Srikakulam, Vizianagaram, East Godavari, and West Godavari districts in Andhra Pradesh, India. Approximately, 80-100 infected fish were examined per site, with documentation of gross clinical signs and parasitic burden. Dactylogyrus spp., Gyrodactylus spp., Myxobolus spp., and Thelohanellus spp. were identified as the primary parasitic agents affecting the carp populations. Infested fish exhibited characteristic symptoms, including respiratory distress, skin darkening, and increased mortality rates. The findings confirmed parasitic infestations as a major challenge in cultivable fish ponds. Notably, Catla catla and Labeo rohita displayed higher susceptibility to Dactylogyrus spp. and myxozoans (Myxobolus spp. and Thelohanellus spp.), respectively. For effective management of parasitic infestation in carp culture, adoption of standard disease management procedures such as applying 25 kg/ha of common salt and 1 L/ha of formalin resulted in lower mortality (1-4%) in experimental tanks in comparison with control tanks (5-13.5%). This study enhances our comprehension of management and preventive approaches for reducing diseases caused by myxozoan and monogenean parasites in aquaculture systems.